Face covering as a social practice: The rhetoric of anti-/masking during the COVID-19 pandemic in the Greek digital public sphere - Kitsiou, Roula (Aegean Working Papers in Ethnographic Linguistics, 2022)
During the COVID-19 pandemic, early public health messages about masking led to public confusion due to conflicting statements, rendering masks a controversial sociopolitical issue. This study employs computer-mediated discourse analysis and tools developed by the discourse-historical approach to explore discourse topics and (anti-/pro-)masking rhetoric patterns in the content of (a) a Greek news video posted on a news site on Facebook, and (b) a corpus of 44 online Facebook comments posted in response to (a). The findings of the study point out that, in the context of the post-truth era, conflicting messages on public health have resulted in politicization of masking and to polarization over socially un-/acceptable behavior. Face covering thus constitutes a sociospatial practice in the process of becoming a form of politic behavior, which is contested among members of Greek society.